Performans Budidaya Ternak Babi Pada Peternak Pesisir: Studi Kasus Kampung Saukorem, Amberbaken-Tambrauw, Papua Barat - Warijo, Saul Jecklin; Iyai, Deny Anjelus; Woran, Djonly; Saragih, Desni; Bajari, Makarius (Jurnal Pertanian Terpadu Santo Thomas Aquinas, 2022)
Understanding the real condition of pig farming in terms of management, feed and livestock production is vital to know. A study on the pig farming system has been carried out in Saukorem village, Amberbaken district, Tambrauw district, West Papua. The research method used is descriptive method with interview and observation techniques. A total of 30 respondents were successfully interviewed and observed the pattern of raising their pigs in the village of Saukorem, Amberbaken District. The results of the study found that the performance of farmers was dominated by elementary school education, with productive age and a sufficient number of family members as workers in the farmer's family. Pig farming business is still done extensively. Pig production is relatively low, this can be seen from the number of pigs in each age group. Pig breeds are obtained from other farmers in the village. The number of cages owned by farmers is still limited. The feed given to farmers comes from kitchen waste and agricultural products with a frequency of 2 times a day. Because the rearing system is still extensive outside the pen, the livestock are susceptible to diseases such as snoring and diarrhea. Livestock treatment is also still carried out by the farmers themselves.